Additional file 1 of Post-traumatic stress disorder among heart disease patients: a clinical follow-up of individuals with myocardial infarction in the Tromsø Study ... - Lorem, Geir Fagerjord; Næss, Eva T.; Løchen, Maja-Lisa; Lillevoll, Kjersti; Molund, Else-Marie; Rösner, Assami; Lindkvist, Sigmund; Schirmer, Henrik (Journal of Epidemiology and Community Health, 2023)
Additional file 1. ...